Air transport and high-speed rail competition: Environmental implications and mitigation strategies. (October 2016) - D'Alfonso, Tiziana; Jiang, Changmin; Bracaglia, Valentina
Highlights: We model air transport-HSR competition's effects on the environment. Market expansion, modal shift, HSR ownership and emissions' heterogeneity play a role. We conduct a simulation study based on the London–Paris market. HSR's introduction has increased LAP but has decreased GHG emissions. Abstract: We build a duopoly model to shed light on the environmental impact of HSR-air transport competition, capturing the effects of induced demand, schedule frequency and HSR speed. The net environmental effect can be negative since there is a the trade-off between the substitution effect – how many passengers using the HSR are shifted from air transport – and the traffic generation effect – how much new demand is generated by the HSR. We conduct a simulation study based on the London-Paris market where HSR has served 70% of the market. The introduction of HSR is detrimental to LAP, while it is beneficial to GHG emissions. HSR entry increases neither LAP nor GHG emissions when the ratio between HSR and air transport emissions is relatively low. Moreover, competition is more likely to be detrimental to the environment when the weight of the social welfare in HSR objective function is high. Since the magnitude of the environmental friendliness of HSR compared to air transport hinges on the mix of energy sources used to generate the electricity (which is heavily constrained by the country in which HSR operates), regulators should assess the implications of HSR entry taking into account the energy policy and mitigation strategies available to transport modes.